Respuesta :

Answer:

N=3

Step-by-step explanation:

Let's solve the given equation:

\[ \frac{5^{n+3}}{25^{2n-3}} = 5^0 \]

We know that \(5^0 = 1\), so the equation becomes:

\[ \frac{5^{n+3}}{25^{2n-3}} = 1 \]

Now, let's express \(25\) as \(5^2\):

\[ \frac{5^{n+3}}{(5^2)^{2n-3}} = 1 \]

Simplify the expression:

\[ \frac{5^{n+3}}{5^{4n-6}} = 1 \]

Apply the rule \(a^m / a^n = a^{m-n}\):

\[ 5^{n+3-(4n-6)} = 1 \]

Combine like terms:

\[ 5^{-3n+9} = 1 \]

Now, equate the exponent to zero:

\[ -3n+9 = 0 \]

Solve for \(n\):

\[ -3n = -9 \]

\[ n = 3 \]

So, \(n = 3\) satisfies the given equation.

Answer:

n=3

Step-by-step explanation:

I'm going to guess that you are saying [tex]\dfrac{5^{n+3}}{25^{2n-3}}=5^0[/tex].

First of all, [tex]a^0=1[/tex] for any [tex]a.[/tex]

[tex]\dfrac{5^{n+3}}{25^{2n-3}}=1[/tex]

Multiply both sides by [tex]\left(25^{2n-3}\right)\neq0[/tex].

[tex]5^{n+3}=25^{2n-3}\implies 5^{n+3}=\left(5^2\right)^{2n-3}[/tex]

Use the exponent rule: [tex]\left(a^m\right)^n=\left(a^n\right)^m=a^{nm}[/tex].

[tex]5^{n+3}=5^{2(2n-3)}\implies 5^{n+3}=5^{4n-6}[/tex]

Use the exponent rule: [tex]a^b=a^c\implies b=c[/tex]

[tex]n+3=4n-6\implies n-4n=-6-3\implies -3n=-9\implies \boxed{n=3}[/tex]

Checking:

[tex]25^{2n-3}\neq0\\\text{Plug in }n=3\implies 25^{2\times3-3}=25^{6-3}=25^3=15625\ne0[/tex]

Therefore, [tex]n=3.[/tex]

Please brainliest?